Psoralen Attenuates Rheumatoid Arthritis through Inhibition of the IL-1β/IL-18/NLRP3 Inflammasome Axis - Wang, Qingwu; Huang, Yu; Li, Jin; Li, Xiang (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Psoralen, a naturally derived compound, is known for its anti-inflammatory properties and thus it is essential to evaluate its effects on inflammatory pathways in Rheumatoid Arthritis (RA). Aim: To assess the anti-RA potential of psoralen by evaluating its effects on protein denaturation, cytokine and inflammasome inhibition, and cell proliferation in RA models and confirm its molecular interactions using molecular docking and simulations. Materials and Methods: Psoralen was tested for anti-inflammatory efficacy utilizing BSA and egg albumin protein denaturation tests and SW-982 and THP-1 cell proliferation assays. Cytokine suppression of IL-1β and IL-18 in THP-1 cells was measured by ELISA and inflammasome expression by western blotting after psoralen administration. After docking using DockThor, molecular dynamics simulations with iMODS and CABS-flex assessed the stability of psoralen interaction with IL-1β, IL-18, and NLRP3 targets. Results: In the BSA assay, psoralen showed significant dose-dependent inhibition, with a maximum inhibition of 88.02±1.96% at 200 mg/mL. Similarly, in the egg albumin assay, psoralen exceeded diclofenac sodium at 200 mg/mL, achieving an absorbance of 2560.80±6.02. Psoralen inhibited cell proliferation in both SW-982 and THP-1 cells, with a more significant effect in SW-982 cells. Docking results showed that psoralen exhibited the highest affinity for NLRP3 (-8.953) compared to IL-1β (-8.206) and IL-18 (-6.504). MD simulations revealed significant flexibility in the binding sites of the complexes, indicating dynamic interactions. Psoralen significantly inhibited IL-1β and IL-18 secretion in THP-1 cells in a concentration-dependent manner. Western blotting analysis demonstrated a dose-dependent inhibition of NLRP3 inflammasome activation. Conclusion: Psoralen effectively modulates the IL-1β/IL-18/NLRP3 inflammasome axis, reducing inflammatory responses and positioning itself as a promising candidate for therapeutic intervention in inflammatory diseases like rheumatoid arthritis. Further in vivo and clinical studies are essential to validate its efficacy, safety profile, and potential mechanisms as an anti-rheumatoid arthritis drug.
Keywords: Cytokines; IL-18; IL-1β; Inflammasome; NLRP3; Psoralen; Rheumatoid Arthritis